The Impact Of International Terrorism On The Right To Personal Security In Iraq After 2003 (UUM Journal of Legal Studies, 2016)
Hardly a day passes by without news of a terrorist bombing, kidnapping, or assassination somewhere in the world especially in Iraq. Terrorism has become a cancer and it is not in the interest of the nations, because it takes away their right to personal security. Following the event of September 11, there have been violations of international conventions and usages, human rights, which prompted countries globally to come up with laws to protect civil freedoms. In the context of Iraq, the Government came up with the Iraqi Anti-Terrorism Act No.13 of 2005 and the Iraqi Constitution of 2005 to address the issue of terrorism. The aim of this paper is to address the impact of international terrorism on the right to personal security in Iraq after 2003. The methodology adopted in this paper is a doctrinal legal research, focusing namely on primary and secondary data. This paper concludes that international terrorism has indeed affected the Iraqis right to personal security after 2003. Hence, there is a need to protect this fundamental right by re-looking into the Iraqi Anti-Terrorism Act No.13 of 2005. For instance, under the Act there is no clear definition of the terms â€œterrorismâ€ and â€œterrorist actâ€. This has led to serious problems in the enforcement of the Iraqi Anti-Terrorism Act No. 13 of 2005 such as the abuse of the right to personal security where innocent Iraqis are deprived to enjoy this fundamental right at the disguise of fighting terrorism by the state, which is not even clearly defined under the Act. Key words: International terrorism, Iraqi Constitution of 2005, Iraqi Anti-Terrorism Act No.13 of 2005, right  to personal security.